Light microscopy of mitochondria at the nanoscale - Jakobs, Stefan (Annu Rev Biophys, 2020)
Mitochondria are essential for eukaryotic live. These double-membrane organelles often form highly dynamic tubular networks interacting with many cellular structures. Their highly convoluted contiguous inner membrane compartmentalizes the organelle, which is crucial for mitochondrial function. Since the diameter of the mitochondrial tubules is generally close to the diffraction limit of light microcopy, it is often challenging, if not impossible, to visualize sub-mitochondrial structures or protein distributions using conventional light microscopy. This renders super-resolution microscopy particularly valuable, and attractive, to study mitochondria. Super-resolution microscopy encompasses a diverse set of approaches that extend the resolution as well as nanoscopy techniques that even overcome the diffraction limit. In this review, we provide an overview on recent studies using super-resolution microscopy to investigate mitochondria, discuss the strengths and opportunities of the various methods to address specific questions in mitochondrial biology and highlight potential future developments.